Near‐Infrared‐II Quantum Dots for In Vivo Imaging and Cancer Therapy - Chen, Lu‐Lu; Zhao, Liang; Wang, Zhi‐Gang; Liu, Shu‐Lin; Pang, Dai‐Wen (Small (Weinheim an der Bergstrasse, Germany), 2022)
In vivo fluorescence imaging can perform real‐time, noninvasive, and high spatiotemporal resolution imaging to accurately obtain the dynamic biological information in vivo, which plays significant roles in the early diagnosis and treatment of cancer. However, traditional in vivo fluorescence imaging usually operates in the visible and near‐infrared (NIR)‐I windows, which are severely interfered by the strong tissue absorption, tissue scattering, and autofluorescence. The emergence of NIR‐II imaging at 1000–1700 nm significantly breaks through the imaging limitations in deep tissues, due to less tissue scattering and absorption. Benefiting from the outstanding optical properties of NIR‐II quantum dots (QDs), such as high brightness and good photostability, in vivo fluorescence imaging exhibits excellent temporal‐spatial resolution and large penetration depth, and QDs have become a kind of promising fluorescent biomarkers in the field of in vivo fluorescence imaging. Herein, the authors review NIR‐II QDs from preparation to modification, and summarize recent applications of NIR‐II QDs, including in vivo imaging and imaging‐guided therapies. Finally, they discuss the special concerns when NIR‐II QDs are shifted from in vivo imaging applications to further in‐depth applications. Near‐infrared‐II quantum dots exhibit outstanding optical properties including tunable emission, excellent fluorescence stability, large Stokes shift, high temporal‐spatial resolution imaging, and large penetration depth, making them overcome the autofluorescence and scattering problems in deep tissue imaging and become promising candidates in the field of fluorescence imaging and therapy in vivo.